Bilateral deep brain stimulation for cervical dystonia in patients with previous peripheral surgery - Capelle, Hans-Holger; Blahak, Christian; Bäzner, Hansjörg (Movement disorders, 2012)
Background: There are no data available concerning whether patients with cervical dystonia who have recurrent or new symptoms after peripheral denervation surgery benefit similarly from pallidal deep brain stimulation compared with patients who receive primarily pallidal stimulation. Methods: Data on 7 cervical dystonia patients with recurrent or progressive dystonia after peripheral denervation who underwent pallidal stimulation were prospectively collected. Deep brain stimulation was performed in Mannheim/Hannover, Germany, or in Umea, Sweden. To the subgroup from Mannheim/Hannover, a second group of patients without previous peripheral surgery was matched. Assessments included the Toronto Western Spasmodic Torticollis Rating Scale and the Burke-Fahn-Marsden dystonia rating scale, as well as the Tsui scale in the Swedish patients. Results: The 4 patients from Mannheim/Hannover experienced sustained improvement from pallidal stimulation by a mean of 57.5% according to the Toronto Western Spasmodic Torticollis Rating Scale (P < .05) and by a mean of 69.5% according to the Burke-Fahn-Marsden dystonia rating scale (P < .05) at long-term follow-up of 40.5 months. The patients from Umea had a mean Tsui score of 7 prior to surgery and a mean score of 3 at the mean follow-up of 8 months (62.5%). In the matched group the Toronto Western Spasmodic Torticollis Rating Scale improved by 58.8% and the Burke-Fahn-Marsden dystonia rating scale by 67% (P < .05) at long-term follow-up (mean, 41.5 months). Conclusions: Patients who had prior peripheral surgery for cervical dystonia experience improvement from subsequent pallidal stimulation that is comparable to that of de novo patients.